PAGET’S DISEASE IN A MALE PATIENT: CASE REPORT - Nyland, Francine Hickmann; Silva, Patrícia Moreira Rebello da; Schorr, Mário Casales; Pedrini, José Luiz (Mastology, 2019)
Paget’s disease is a rare entity that accounts for 1 to 3% of breast tumors. Occurrence in male patients is even less common. Literature has reported only 24 cases in the last 20 years. We described the case of a 62-year-old male patient that sought medical care due to erosion and eczema on left nipple. After skin biopsy, the clinical suspicion of Paget’s disease was confirmed by histological and immunohistochemical studies, which enabled the proper surgical and oncological treatment.